2013
DOI: 10.1111/ijac.12016
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Ultrafine Hafnium Diboride Powders Using Solution‐Based Processing and Spark Plasma Sintering

Abstract: Ultrafine hafnium diboride (HfB2) powders were synthesized by the boro/carborthermal reduction process. Fine‐scale mixing of the reactants was achieved by solution‐based processing using hafnium oxychloride (HfOCl2·8H2O) and phenolic resin as the precursor of HfO2 and carbon respectively. The heat treatment was completed at a temperature range 1300–1500°C for 1h using spark plasma sintering (SPS) apparatus. The crystallite sizes of the synthesized powders were small (<500 nm) and the oxygen content was low (0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Recent reports showed that the synthesis of ceramic powders in PECS furnace with specially designed die/punch/sample set-up required lower temperature and shorter time than traditional method, and the obtain powders had smaller particle size. [14][15][16] In this paper, B 4 C-TiB 2 composite powders were prepared using pulsed electric current heating (PECH) in PECS furnace using TiC and amorphous B as raw materials according to reaction (2) with x = 1.0. The effects of temperature, dwelling time on the phase composition, particle size and morphology were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports showed that the synthesis of ceramic powders in PECS furnace with specially designed die/punch/sample set-up required lower temperature and shorter time than traditional method, and the obtain powders had smaller particle size. [14][15][16] In this paper, B 4 C-TiB 2 composite powders were prepared using pulsed electric current heating (PECH) in PECS furnace using TiC and amorphous B as raw materials according to reaction (2) with x = 1.0. The effects of temperature, dwelling time on the phase composition, particle size and morphology were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The peak in the 1292 cm −1 is attributed to the stretching vibration of C-CH 3 and in-plane bending vibration of C-H of acetylacetone ligand. 10,25 The absorption peak at 427 cm −1 in acidic conditions can be devoted to stretching vibration of Hf-O bonds along with a decrease in peak intensity and a small shift to the lower wavenumber in neutral sample (413 cm −1 ), indicating the interaction between C = O group and Hf atom having higher bond lengths and less intramolecular hydrogen bonding in neutral conditions (Figure 9). 26,56 From the FTIR spectrum of the polymeric precursor derived from acidic conditions, the characteristic absorption peaks of 845, 1023, and 1170 cm −1 are, respectively, assigned to vibration of Hf-O-Hf, 57 Hf-O-C, and Hf-O-C-B bonds.…”
Section: Ftir Analysis Of Precursor Fibers Prepared Under Differentmentioning
confidence: 99%
“…11 The main weight loss of ~40% in the range 350-460°C accompanied by sharp exothermic peak near 452°C in the DSC curve can be attributed to the polycondensation and crosslinking of the polymer, gas evolution of H 2 O, N 2 , and CO 2 or CO, 26 the decomposition of chelated hafnium diketonate structure, 67 and crystallization of monoclinic hafnia (m-HfO 2 ). 10,45 The weight loss of ~10% in the range 460-1000°C with the exothermic peak in the DSC at 842°C may be caused by the crosslinking of HfB 2 precursor and transformation of amorphous HfO 2 to tetragonal hafnia (t-HfO 2 ). 26 The smooth weight loss (~2%) from 1000°C to 1500°C corresponding to the endothermic peak at 1102°C in the DSC curve would be assigned to the carbothermal reduction reaction for HfB 2 formation.…”
Section: Ftir Analysis Of Precursor Fibers Prepared Under Differentmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, modified SPS processes have been used for synthesizing ceramic compound powders. 3,[14][15][16][17][21][22][23][24] The size of the starting powder has a significant effect on the densification behavior. Reducing the particle size to nanoscale has been shown to be an efficient way to enhance densification at lower sintering temperatures.…”
Section: Introductionmentioning
confidence: 99%